Penerapan Data Mining Prediksi Jumlah Wisatawan Menggunakan Algoritma Regresi Linear Berganda - dikesuma, hendra; Yanto, Robi; Alfiarini, Alfiarini; Ahmadi, Ahmadi (Teknik Komputer Politeknik Negeri Sriwijaya, 2024)
Lubuklinggau is known as a transit city which is located directly on the border with 2 provinces, namely Bengkulu and Jambi. The city of Lubuklinggau has a tourism program known as